Using Epistemology to Hack Islamic Management - Moh. Nurul Qomar; Athi’ Hidayati; Nafi’uddin Nafi’uddin (ITB AAS INDONESIA Surakarta, 2022)
Western epistimology departs doubt for truth, while Islamic epistemology departs on belief. The purpose of this study is to discover an epistemology of Islamic management that references to the Qur'an as a source of knowledge in Islam. Qualitative research is used as a research approach to acquire a thorough grasp of the study topic. The study data is gathered utilizing library research methodologies, beginning with the discovery of many verses in the Qur'an that are both relevant and substantively connected to management. Furthermore, by doing interpretation and context analysis, the verse is demonstrated to be connected to management. According to the findings of this study, the epistemology of Islamic management is split into two categories: tawhid epistemology and operational epistemology. The aim of monotheistic epistemology based on tawhid is to combine the notion of tawhid with the concept of Islamic management; without the concept of tawhid, it is impossible to accomplish ridho Allah SWT. The goal of operational epistemology is to include the concepts of responsibility, transparency, trust, justice, professionalism, and accountability into Islamic management systems as a form of devotion to Allah. SWT.